Critical shoot phosphorus concentrations for changes in root morphology to improve phosphorus uptake in cotton. Issue 1 (5th January 2023) - Chen, Bolang; Feng, Lin; Gu, Huimin; Zhang, Man; Chai, Zhongpin; Feng, Gu
Abstract: Background: In recent years, the response of cotton ( Gossypium hirsutum L.) root morphology and rhizosphere processes to phosphorus (P) deficiency have attracted extensive attention. However, the dynamics of root morphology and physiology to shoot P concentration (SPC) under various P conditions remain unclear. Aim: We aimed to determine the changes in root morphology and physiology and their relationships with SPC under different levels of P supply. Method: The cotton cultivars XLZ13 and XLZ19 were grown in a hydroponic experiment with seven rates of P supply (0–2.0 mM P L −1 ) and in a root box experiment with seven P levels (0–400 mg P kg −1 ). Root morphological and physiological parameters were determined 60 days after planting (hydroponic experiment) and 75 days after transplanting (root box experiment). Results: Cotton plant growth, P uptake, and root morphology differed significantly between the two genotypes and among the P levels. Cotton plants had the maximum shoot biomass when the SPC of XLZ13 and XLZ19 were 4.6–5.9 mg g −1 and 3.9‐5.0 mg g −1, respectively. Total and specific root lengths initially increased with increasing SPC and peaked at an SPC of XLZ13 and XLZ19 about 6.0–7.0 mg g −1 and 4.0‐5.0 mg g −1, respectively. Root physiological responses (rhizosphere acidification, acid phosphatase [Apase] activity) decreased as the SPC increased. Conclusions: The critical SPC for optimal root morphology were 5–6 mg g −1 . P deficiency did not induce rhizosphere acidification but promoted root and rhizosphere APase activity.